1998
DOI: 10.2337/diabetes.47.12.1953
|View full text |Cite
|
Sign up to set email alerts
|

Vascular permeability in experimental diabetes is associated with reduced endothelial occludin content: vascular endothelial growth factor decreases occludin in retinal endothelial cells. Penn State Retina Research Group.

Abstract: Blood-retinal barrier (BRB) breakdown is a hallmark of diabetic retinopathy, but the molecular changes that cause this pathology are unclear. Occludin is a transmembrane component of interendothelial tight junctions that may regulate permeability at the BRB. In this study, we examined the effects of vascular endothelial growth factor (VEGF) and diabetes on vascular occludin content and barrier function. Sprague-Dawley rats were made diabetic by intravenous streptozotocin injection, and age-matched animals serv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

14
312
1
7

Year Published

2004
2004
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 534 publications
(338 citation statements)
references
References 11 publications
14
312
1
7
Order By: Relevance
“…The reduced expression of TJ protein occludin may shed some light on the HG-induced barrier hyperpermeability and support the previous in vivo studies reporting a direct correlation between the levels of TJ proteins and the extent of endothelial barrier permeability. [26][27][28] The discontinuous appearances of occludin and ZO-1 on cell periphery provide further explanation for the HG-mediated increases in paracellular flux. Consistent with the recent data showing an insulin-mediated elevation in the cerebral contents of occludin and ZO-1, normalization of glucose levels in our study also significantly improved occludin levels and effectively restored occludin and ZO-1 staining to the cell periphery, a set of findings replicated by inhibitions of RhoA or Rho-kinase.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The reduced expression of TJ protein occludin may shed some light on the HG-induced barrier hyperpermeability and support the previous in vivo studies reporting a direct correlation between the levels of TJ proteins and the extent of endothelial barrier permeability. [26][27][28] The discontinuous appearances of occludin and ZO-1 on cell periphery provide further explanation for the HG-mediated increases in paracellular flux. Consistent with the recent data showing an insulin-mediated elevation in the cerebral contents of occludin and ZO-1, normalization of glucose levels in our study also significantly improved occludin levels and effectively restored occludin and ZO-1 staining to the cell periphery, a set of findings replicated by inhibitions of RhoA or Rho-kinase.…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with the recent data showing an insulin-mediated elevation in the cerebral contents of occludin and ZO-1, normalization of glucose levels in our study also significantly improved occludin levels and effectively restored occludin and ZO-1 staining to the cell periphery, a set of findings replicated by inhibitions of RhoA or Rho-kinase. [26][27][28] Subsequent studies focusing on the specific impact of PKC-b on cerebral endothelial cell content of TJ proteins have shown that knockdown of PKC-b significantly increased occludin and ZO-1 protein levels under hyperglycemic conditions and selectively that of occludin also under normoglycemic conditions. Decreases in phosphorylation, ubiquitination, and trafficking of occludin may account for the PKC-b-inhibition-mediated improvements observed in occludin protein levels.…”
Section: Discussionmentioning
confidence: 99%
“…The role of an alteration in endothelial cell junction adhesion in diabetes-induced permeability has been supported by studies showing a decreased level of the tight junction protein occludin in rats rendered diabetic with streptozotocin or treated with intraocular injections of VEGF (Antonetti et al, 1998;Barber et al, 2000). The VEGF-induced hyperpermeability response appears to be associated with phosphorylation of occludin and another junction protein, ZO-1 (Antonetti et al, 1999a).…”
Section: Vegf and Vascularmentioning
confidence: 98%
“…1,2 Although the exact mechanism of ME in BRVO is not fully understood, ME is thought to be caused by the flux of fluid from the blood vessels to the tissue, because of breakdown of the blood-retinal barrier as a result of damage to the tight junctions of capillary endothelial cells, enhanced expression of inflammatory cytokines such as prostaglandins and interleukin 6, and increased secretion into the vitreous of vasopermeability factors such as vascular endothelial growth factor (VEGF) produced in the retina. [3][4][5][6][7] Several recent studies have reported that VEGF has an important role in the pathophysiology of ME by inducing blood-retinal barrier breakdown and increasing vascular permeability. [6][7][8][9] Elevated VEGF level in vitreous has been reported in patients with BRVO, and this elevation was correlated with the severity of ME and area of non-perfusion.…”
Section: Introductionmentioning
confidence: 99%